National Priority Projects and the Issues of Forest Encroachment (Scientific Researches in Academia, 2024)
Forests are one of the major land-use systems in Nepal, covering 45.31% of the total land of the country as per the Economic Survey, 2080/81. Forest heritage is amongst the forms of natural heritage. Forests of Nepal as well as biodiversity are requisite to both the livelihoods as well as for the environmental conservation. Nepal has an ecologically diverse landscape providing home to many species of flora and fauna. But forest encroachment has been turned out to be one of the major challenges in the protection and conservation of the forest, environment and the biodiversity. In addition, the major focus of the government on conducting the projects of national priority have in one way or the other caused the higher uses of the forest area. Therefore, this paper attempts to provide an overview of the forest encroachment in context of Nepal along with the causes specifically addressing to that of infrastructural development issues. Moreover, the paper tries to examine the varied impacts of forest encroachment in Nepal posed by the national pride projects.